IntraCoronary Artery Retrograde Thrombolysis vs. Thrombus Aspiration in ST-Segment Elevation Myocardial Infarction: Study Protocol for a Randomized Controlled Trial - Shen, Mingzhi; Wang, Jihang; Li, Dongyun; Zhou, Xinger; Guo, Yuting; Zhang, Wei; Guo, Yi; Wang, Jian; Liu, Jie; Zhao, Guang; Zhao, Shihao; Tian, Jinwen (Frontiers in Cardiovascular Medicine, 2022)
Background: Type 2 diabetes (T2DM) is a major risk factor for myocardial infartion. Thrombus aspiration was considered as a good way to deal with coronary thrombus in the treatment of acute myocardial infarction. However, recent studies have found that routine thrombus aspiration does not benefit. This study is designed to investigate whether intracoronary artery retrograde thrombolysis (ICART) is more effective than thrombus aspiration or percutaneous transluminal coronary angioplasty (PTCA) in improving myocardial perfusion in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI). Methods/design: IntraCoronary Artery Retrograde Thrombolysis (ICART) versus thrombus aspiration or PTCA in STEMI trial is a single-center, prospective, randomized open-label trial with blinded evaluation of endpoints. A total of 286 patients with STEMI undergoing PPCI are randomly assigned to two groups: ICART, and thrombus aspiration or PTCA. The primary endpoint is the incidence of >70% ST-segment elevation resolution. Secondary outcomes include distal embolization, myocardial blush grade, TIMI flow grade, in-hospital bleeding. Discussion: The ICART trial is the first RCT clinical trial to date to verify the effect of ICART versus thrombus aspiration or PTCA on myocardial perfusion in patients with STEMI undergoing PPCI.